Cattle Disease Diagnosis Expert System in Bandes Village, Ainaro District - Marito De Oliveira Amaral Barreto; Rina Dewi Indahsari (Universitas Muhammadiyah Sidoarjo, 2021)
Most of the people in the Bandes village of Ainaro district work as breeders. Cows that are raised are beef cattle. One of the obstacles that exist in Bandes Village is the existence of a few veterinarians in Bandes Village. This research discusses an expert system for diagnosing diseases in cattle, which functions to help determine the disease that is being suffered by cattle, this system will display the results of the diagnosis in the form of the name of the disease, a description of the disease solution and its prevention. In this study there were 4 diseases studied and 7 symptoms. From the 4 disease data, isolation of the problem area, target decision and dependency diagram is made. After that the formation of IF – THEN rules, after the rules are made, the backward chaining process is made. So as to produce a solution to overcome disease in cattle. In program testing is done by comparing the results of the system with experts. In the trials that have been carried out, the results obtained are appropriate or the accuracy of the data and facts obtained from experts on cattle. So based on the results of tests that have been carried out on the system as much as 4 data, the accuracy value obtained is 100% accurate which shows that the expert system is functioning properly in accordance with the expert's diagnosis